A satellite-derived glacier inventory for North Asia. Issue 71 (March 2016) - Earl, Lucas; Gardner, Alex
Abstract: This study outlines a consistent methodology for identifying glacier surfaces from Landsat 5, 7 and 8 imagery that is applied to map all mainland North Asian glaciers, providing the first methodologically consistent and complete glacier inventory for the region 2010. We identify 5065 glaciers covering a planimetric area of 2326 ± 186 km 2, most of which is located in the Altai mountain subregion. The total glacier count is 15% higher, but the total glacier area is 32 ±11.6% lower, than the estimated glacier coverage provided in version 4.0 of the Randolph Glacier Inventory. We investigate the distribution of glacier size within North Asia and find that the majority of glaciers (82%) are smaller than 0.5 km 2 but only account for a third of the total glacier area, with the largest 1 % (60 glaciers ≥ 5 km 2 ) accounting for 28% of the total area. We present hypsometric characterizations of North Asian glaciers, largely substantiating existing findings that glaciers in this region are dominated by cold, relatively dry conditions. We provide a detailed assessment of errors and determine the uncertainty in our area estimate to be ±8.0%, with snow-cover uncertainty the largest contributing factor. Based on this assessment, the new glacier inventory presented here is more complete and of higher quality than other currently available data sources.